Innovative Concepts for Alternative Migration Policies Ten Innovative Approaches to the Challenges of Migration in the 21st Century - Jandl, Michael (IMISCoe Reports, 2007)
Based on the strengths of combined ideas from migration researchers, policy experts, and representatives of international organisations, this timely volume provides eight basic principles for the design of innovative migration policy. Presents new proposals for innovative migration policies.